La ricezione dei film di Roberto Rossellini nei periodici cinematografici polacchi dal 1946 al 1956 - Miller-Klejsa, Anna (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In this article I focus on examining the reception of Roberto Rossellini’s filmsin Polish film journals (period: 1946-1956) and cultural magazines. The analysis showsthat while Rossellini’s first post-war film – Roma città aperta – was positively received inthe People’s Republic of Poland until 1949, from the early 1950s onwards – i.e. duringthe Stalinist period – there was a rather critical turn, as Soviet cinema and the poetics ofsocialist realism came to the fore. From this moment on, Italian neo-realism was accusedof pessimism and of having lost its “great revolutionary prospects”. This critical attitudechanged during the so-called thaw period, when neorealism became a kind of referencemodel. However, because of their explicit religious themes, some neo-realist films werenot allowed by the censorship in the Polish film circuit; as a consequence, some Rossellini’sfilms were never screened in cinemas in the People’s Republic of Poland.